Comparative Study of Voltammetric Analysis with UV-Vis Spectrophotometry in Determining the Results of Liquid-Liquid Extraction of Samarium (III) - Wyantuti, Santhy; Nurwulanda, Salsha; Mardiah, Najmah; Anggraeni, Anni; Pratomo, Uji; Fauzia, Retna Putri; Bahti, Husein H. (Syarif Hidayatullah State Islamic University, 2024)
Rare earth elements (REEs) are garnering significant attention in diverse fields due to their important and fascinating properties. Among these REEs, samarium (Sm) has numerous advantages and benefits. Before using Sm, it must be separated from its natural sources due to the formation of complex compounds with other elements. To achieve this, liquid-liquid extraction emerges as one of the REE separation methods, presenting several advantages, including a streamlined process. Various methods can be used to analyze extraction results, such as ICP-MS and XRF. In comparison, UV-Vis spectrophotometry has significant advantages compared to other methods, it provides a simple approach to determining the level of a substance, and the results given are quite accurate, while differential pulse voltammetry (DPV) is one of the electrochemical analysis methods that is expected to provide faster and accurate analysis results. This study aims to determine the value of analytical parameters, Kd of Sm(III) liquid-liquid extraction results using DPV analysis and UV-Vis spectrophotometry methods. The DPV method yielded LoD 1.24 mg/L, accuracy 98.39%, and %recovery 106.69%. The extraction data obtained Kd Sm values ranging from 6.0019-7.3860. The UV-Vis spectrophotometry results provided an individual extraction efficiency of Sm(III) of 88.54%. This method obtained LoD 0.71 mg/L, accuracy 96.00%, and %recovery 104.00%.